Adipose-Derived Stem Cells from Both Visceral and Subcutaneous Fat Deposits Significantly Improve Contractile Function of Infarcted Rat Hearts. Issue 11 (November 2015) - Chi, Chao; Wang, Fei; Xiang, Bo; Deng, Jixian; Liu, Shangdian; Lin, Hung-Yu; Natarajan, Kanmani; Li, Gang; Wang, Lei; Wang, Jian; Lin, Francis; Freed, Darren H.; et al.
Adipose-derived stem cells (ASCs) from subcutaneous and visceral adipose tissues have been studied individually. No studies have compared their abilities in treatment of heart failure. This study was designed to evaluate whether ASCs from the two sources could provide a long-term improvement of cardiac function in infarcted hearts. Rat subcutaneous and visceral adipose tissues were excised for isolation of ASCs. Morphology, yield, proliferation, surface markers, differentiation, and cytokine secretion of the subcutaneous ASCs (S-ASCs) and visceral ASCs (V-ASCs) were analyzed. Then a rat model of myocardial infarction (MI) was established by a coronary occlusion. Seven days after occlusion, S-ASCs ( n = 22), V-ASCs ( n = 22), and Dulbecco's modified Eagle medium (DMEM, n = 20) were injected into the infarct rim, respectively. Cardiac function was then monitored with MRI for up to 6 months. The hearts were then removed for histological assessments. The yield of V-ASCs per gram of the visceral adipose depot was significantly greater than that of S-ASCs in 1 g of the subcutaneous adipose depot. On the other hand, the S-ASCs showed a greater proliferation rate and colony-forming unit relative to the V-ASCs. In addition, the infarcted hearts treated with either S-ASCs or V-ASCs showed a significantly greater left ventricular ejection fraction (LVEF) than those treated with DMEM at 4 weeks and 6 months following the cell/DMEM transplantation. Moreover, the infarct sizes of both S-ASC- and V-ASC-treated hearts were significantly smaller than that in the DMEM-treated hearts. MRI showed the implanted ASCs at the end of 6 months of recovery. Despite the differences in cell yield, proliferation, and colony formation capacity, both S-ASCs and V-ASCs provide a long-lasting improvement of cardiac contractile function in infarcted hearts. We conclude that the subcutaneous and visceral adipose tissues are equally effective cell sources for cell therapy of heart failure.